2015
DOI: 10.1002/adom.201500380
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Luminescence, Collective Heating, and Nanothermometry in an Ensemble System Composed of Lanthanide‐Doped Upconverting Nanoparticles and Gold Nanorods

Abstract: A combined system of gold nanorods and NaGdF 4 :Er 3+ /Yb 3+ upconverting nanoparticles with double functionality, luminescence enhancement, and monitored heating is introduced. The paired nanostructures could become an excellent optical heater with thermal probe incorporated. To study their interaction, the longitudinal surface plasmon resonance of the gold nanorods is tuned to 980 nm, in resonance with the Yb 3+ absorption wavelength, so they can be simultaneously excited. Gold nanorods create a localized el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 50 publications
1
70
0
Order By: Relevance
“…Hence, Au nanorods with 850 and 980 nm LSPR bands produce, respectively, a 49.7 and 77.9 % temperature increase over the 308 K measured for bare (Gd,Yb,Er) 2 O 3 nanorods (102 W cm −2 ). When compared with NRs‐AuNRs‐1.25, Au nanorods present a stronger heating effect due to the presence of longitudinal LSPR bands (Figure A–B), in accord with previous work . In particular, NaGdF 4 :Er 3+ /Yb 3+ upconverting nanoparticles mixed with Au nanorods reveal a 150 K increase in temperature when irradiated with a laser power density of 20 W cm −2 (corresponding to an increase of 7.5 K W −1 cm 2 ) .…”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…Hence, Au nanorods with 850 and 980 nm LSPR bands produce, respectively, a 49.7 and 77.9 % temperature increase over the 308 K measured for bare (Gd,Yb,Er) 2 O 3 nanorods (102 W cm −2 ). When compared with NRs‐AuNRs‐1.25, Au nanorods present a stronger heating effect due to the presence of longitudinal LSPR bands (Figure A–B), in accord with previous work . In particular, NaGdF 4 :Er 3+ /Yb 3+ upconverting nanoparticles mixed with Au nanorods reveal a 150 K increase in temperature when irradiated with a laser power density of 20 W cm −2 (corresponding to an increase of 7.5 K W −1 cm 2 ) .…”
Section: Figuresupporting
confidence: 89%
“…Accordingly, the highest temperature increment was observed for NRs‐AuNRs‐980 nm‐C platforms (Figure B). However, these nanoplatforms have several limitations due to the resonance of the LSPR band with the excitation wavelength: (i) there is competition between LSPR and Yb 3+ absorption, reducing the Yb 3+ ‐to‐Er 3+ energy transfer efficiency and quenching Er 3+ emission; and (ii) the Er 3+ emission may be also quenched by Er 3+ ‐to‐Au energy transfer . Therefore, the optimal condition for Er 3+ 2 H 11/2 → 4 I 15/2 and 4 S 3/2 → 4 I 15/2 upconversion emission at the lowest possible laser power density (ca.…”
Section: Figurementioning
confidence: 99%
“…lanthanide ion doped NPs or dye molecules) significantly enhances the luminescence efficiency or quenches their emission. [11,18] HNPs can be used for both in vivo fluorescence imaging and PTT.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that the combination of gold nanorods and UCNPs deposited on thin films can function as a plasmon-enhanced nanothermometric structure 194 . Gold nanorods showed collective heating upon surface plasmon activation, which in turn tuned the green-to-red emission ratio of the UCNPs.…”
Section: Plasmonic Enhancement and Other External Resonatorsmentioning
confidence: 99%